Safeguards Assessments : 2006 Update. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
This paper provides Executive Directors with an update of safeguards assessment activities through the first half of 2006. This is the first update report following the review of the safeguards policy in April 2005, when Directors agreed that such reports should be prepared on an annual basis going forward rather than on a semi-annual basis.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Central Bank Counterpart; Central Bank; Policy Review; Policy; PP; Haiti